REDESIGN PERFORMANCE MEASUREMENT SYSTEMS: A LITERATURE REVIEW - Rois Syarif Qoidhul Haq (Journal of Risk and Uncertainty Issues, 2022)
Performance evaluation must be continuously redesigned considering that there are still many employees who feel uncomfortable with the ongoing performance evaluation, due to several problems that common happened. Based on the literature review perspective, it was concluded that in improving employee performance, the redesign of performance measurement systems relies on design recommendations. The recommendation refers to strengthening the function of the performance-based reward system which includes several important elements of performance for employees, such as the quantity of results, quality of results, timeliness of results, attendance, and ability to work together.